Microstructure Control of Secondary A 231 Cast Alloy Used in Automotive Industry - Hurtalova, Lenka; Tillova, Eva; Chalupova, Maria; Belan, Juraj; Vasko, Alan (Manufacturing Technology Journal, 2014)
The application of Al-Si alloy castings has gradually increased in many mechanical components in the last years, especially for cars and rail vehicles, thanks to the great potential of these materials as replacements for ferrous alloys. Controlling the microstructure of secondary aluminium cast alloy (Al-scrap and workable Al-garbage) is very important, because these alloy containing more of additions elements, that forming various intermetallic phases in the structure. The mechanical properties are strongly depending on the morphologies, type and distribution of the structural parameters. Microstructure control was realized with combination of different analytical techniques (light microscopy, scanning electron microscopy (SEM) upon deep etching and energy dispersive X-ray analysis - EDX).
Keywords: Al-Si cast alloy; mechanical properties; SEM; deep etching; X-ray analysis